RELAY KOORDINASI PROTEKSI OVER CURRENT RELAY(OCR) PADA SISTEM IEEE 7 BUS MODIFIEDBERBASIS ARTIFICIAL NEURAL NETWORK(ANN) - Bayu Dwi Prabowo; Arif Harjanto; Nur Rani Alham; Restu Mukti Utomo; Tantra Diwa Larasati (Universitas Nusa Cendana, 2023)
The procurement electricity increases every year, therefore concept distributed generation is used. To maintain the quality of distribution is used a good Over Current Relay (OCR) setting to overcome Short Circuit in an IEEE Modified 7 Bus Electric Power system. Relay settings used 2 calculations are manual calculations and ANN method. Adaptive relay calculations distributed generation system are divided 4 conditions. The ANN method is used to see the error value coordinate. The results calculations using the ANN method obtained MSE value 3,91e-14. Total TDS and IPickup results in condition 1 are 1,355328s and 38,6715, in condition 2 are 1,199314s and 35,5915, in condition 3 are 1,30228s and 27,1915 and in condition 4 are 1,17221s and 24,304. While the results ANN method in condition 1 are 1,355349s and 38,671495, in condition 2 are 1,199338s and 35,591495, in condition 3 are 1,302281s and 27,191494 and in condition 4 are 1,172241s and 24,303997. The results of relay coordination in accordance with the design in conditions 1 and 2. Conditions 3 and 4 with the location fault on Bus 2 Backup relay R3 is replaced with R6, this occurs due to a change in the direction of the fault current in the system.